Partitioning of Oracle Application in Structured Electronic Medical Records - Chaundi Pan; Jiandong Hu; Jian Shi (Institute of Advanced Engineering and Science, 2014)
This paper described how to use Oracle partitioning to achieve classified storage of data from structured electronic medical records. Because structured electronic medical records stored massive data, the performance, security and stability of database had been paid more and more attentions. In this paper, table with partition in structured electronic medical records system was presented to solve these problems. In addition, testing of comparing the performance of table with and without partition had been taken to prove it was much faster to retrieve partitioned tables with massive data than not partitioned tables.